Muito além de Leonel Brizola: a encampação e a desapropriação da AMFORP em Porto Alegre (1959) - Bastos, Lauren dos Reis (2020)
This dissertation aims to study the circumstances surrounding the expropriation of the American & Foreign Power Company (AMFORP), which took place in 1959, through the perspective offered by the case 7606, which was processed in the local justice of Porto Alegre, Rio Grande do Sul. AMFORP was an electricity public utility company based in the United States, which came to be installed in Brazil in 1927 and in the state of Rio Grande do Sul in 1928, generating and supplying energy to the capital. During the period in which it developed its business activity, the company was accumulating clashes with politicians, industrialists and other consumers, having its performance questioned since 1939, when the mayor Loureiro da Silva expressed dissatisfaction with contractual clauses signed for the concession. However, the issue only gained a solution in the state government of Leonel Brizola, whom was associated with the expropriation initiative when, in reality, the mobilization to recovery the service happened earlier. The objective is to add a different perspective to the existing studies about this subject, what consists of bringing to the scene of events what unrolled within the Law, from the analysis of the case. Thus, the study addresses the precedence of the US Company, its attribute of origin and strategies designed for international expansion and investment, which together with the national characteristics, allowed it to transform the initial Brazilian market into its most lucrative businesses. Likewise, presents the contractual and by-law characteristics that signed it in Porto Alegre, as well as the effects that Brazilian law had on the company's activity. The historical context in which the expropriation takes place refers to the antagonism between two proposals of power, namely nationalism and imperialism. The sources used in the research lead to process n° 7606 for the expropriation of the company properties, laid up at the Memorial of the Court of Justice of Rio Grande do Sul, although its place of custody is the Central Archive of that same institution. This is the main source that provides the substrate for the analysis of the recovery, contrasting the reproduction of Leonel Brizola's narrative and revealing essential issues for the understanding of the expropriation of the American company. In order to articulate the elements of History and Law present in the dissertation, a method was chosen a hermeneutic and qualitative approach that will unveil the aspects related to the indemnity, the defense arguments, appeals, proofs and the contrasts between the decisions produced in the offices. From a systemic interpretation, which includes the laws, the political scenario and the growing anti-imperialist discourse, it was possible to achieve the result that revealed the specifics existing in the expropriation of AMFORP, as well as its trajectory in the thirty years of activity in Porto Alegre.